Ag-TiO2/EVA Composites for Wood Preservation: Antibacterial, Anti-mold, and Anti-Discoloration Performance - Ting Liu; Yaoxing Sun; Honggang Zhao; Huachun Qi; Jiuyin Pang (BioResources)
Ag-TiO2/EVA composites were synthesized using silver-loaded nano TiO2 (Ag-TiO2) and ethylene-vinyl acetate (EVA) emulsion as raw materials, aiming to develop functional materials with antibacterial, anti-mold, and anti-discoloration in properties for wood protection. The study systematically evaluated the composites’ inhibition efficacy against discoloration fungi and molds, long-term antibacterial performance, as well as the tensile strength and water vapor transmission rate of composite films. Experimental results demonstrated that 100% inhibition efficacy against Botryodiplodia theobromae and Aspergillus niger was achieved under two optimal conditions: film thickness of 0.12 to 0.15 mm with Ag-TiO2 loading ≥20%, or film thickness of 0.18 to 0.21 mm with Ag-TiO2 loading ≥15%. Samples with 10%, 15%, and 20% Ag-TiO2 loading exhibited >99.99% antibacterial rates against both Escherichia coli and Staphylococcus aureus. Notably, the 20% Ag-TiO2 sample retained high antibacterial values of 93.0% and 91.7% against these bacteria after 15 days of storage. Mechanical and barrier property tests revealed that compared to the control, the tensile strength of composite films increased by 19.8%, 24.6%, and 29.3% at Ag-TiO2 loadings of 10%, 15%, and 20% respectively, while water vapor transmission rates decreased by 48.6%, 52.9%, and 60.6%. These findings collectively confirm that Ag-TiO2/EVA composites possess excellent bactericidal effects and significant wood anti-mold/anti-discoloration functionality.